Optimizations of Autonomous Mobile Drawers for Industry - Sazali, Sarah Nur Syahirah binti; Roslan, Hazli (Progress in Engineering Application and Technology, 2021)
In the global industrial sector, robots are evolving rapidly from powerful stationary machines to a more complex mobile platform to meet a wider range of automation needs. One of the most innovative automation solutions to some of the problems faced in the industries are definitely the Autonomous Mobile Robots [1]. Deploying Autonomous Mobile Robots in an industrial environment is not an unusual concept, especially in this modern era. The technical specifications and applications of these robots could vary from warehouse to offshore uses [2]. Technologies advancement of these robot have reached a peak where they are capable of doing everything on their own, such as monitoring their battery level and returning to their charging port if the battery is lower than certain values. But with every out of the ordinary technical specs comes a great cost. Thus, businesses that are still developing would not be able to install such advanced technologies. Therefore, in this project a similar kind of automated mobile robot that are able to retain the notion of independence, basic functionalities, and can be built at a lower cost will be discussed. The robot is designed to be a drawer and will navigate its own way by following a black line. To ensure it does so safely without any collisions, it will be equipped with Ultrasonic Sensors to sense any obstructions that are in its way. Lastly, the robot will confirm its location with the use of Radio Frequency Identification system.